2009
DOI: 10.4028/www.scientific.net/kem.421-422.289
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Behavior of Silver Particles in Electrode for Multilayer Ceramic Substrate

Abstract: Several types of Ag powder were used as electrode paste for a multilayer ceramic substrate. The shrinkage behavior of the silver powders was investigated during the sintering. Bending and cracking were frequently observed on the substrate when coarse powders that show a broad size distribution and aggregation were used. The shrinkage curve of the Ag paste obtained by spray pyrolysis agreed well with that of the substrate. Furthermore, the electrical properties of the Ag paste were also determined. The resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…When the sintering time was 600 s, the specific resistivity of the silver paste sintered at 700ºC and 900ºC was 2.97 × 10 -8 Ωm and 2.15 × 10 -8 Ωm, respectively. The silver paste exhibited low resistivity of the order of 10 -8 Ωm, which was in agreement with that of the silver paste used for low temperature co-fired ceramics [19,20]. When the sintering time was 3,600 s, the specific resistivity of the silver paste sintered at 700ºC and 900ºC was 1.94 × 10 -8 Ωm and 1.89 × 10 -8 Ωm, respectively.…”
Section: Sintering and Electrical Properties Of Silver Pastesupporting
confidence: 79%
See 1 more Smart Citation
“…When the sintering time was 600 s, the specific resistivity of the silver paste sintered at 700ºC and 900ºC was 2.97 × 10 -8 Ωm and 2.15 × 10 -8 Ωm, respectively. The silver paste exhibited low resistivity of the order of 10 -8 Ωm, which was in agreement with that of the silver paste used for low temperature co-fired ceramics [19,20]. When the sintering time was 3,600 s, the specific resistivity of the silver paste sintered at 700ºC and 900ºC was 1.94 × 10 -8 Ωm and 1.89 × 10 -8 Ωm, respectively.…”
Section: Sintering and Electrical Properties Of Silver Pastesupporting
confidence: 79%
“…The shrinkage of silver paste drastically decreased from 600°C and reached 12 % at 900°C. We have been reported that silver powder with a broad particle size distribution generally led to the large shrinkage [18,19]. In this work, we considered that the shrinkage of silver paste became large because silver powder classified had a broad particle size distribution.…”
Section: Sintering and Electrical Properties Of Silver Pastementioning
confidence: 99%
“…The coated Ag paste on one side of the precursor induces thermal stress during the whisker growth process. The volume of Ag paste was reported to shrink by 20% at high temperatures due to evaporation of the solvent. , Figure displays the optical and scanning electron microscopy (SEM) images for the (a) as-prepared precursor and (b) Ag paste-coated precursor after annealing for whisker growth. The as-prepared precursor exhibited no remarkable deformation or whisker growth, whereas the paste-coated one was strongly bent and produced whiskers.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the silver paste exhibited low resistivity of the order of 10 ¹8 ³ m, which is in agreement with that of the silver paste used for low-temperature co-fired ceramics. 25) The specific resistivity of the silver paste sintered for 60 min decreased from 2.33 © 10 ¹8 to 2.11 © 10 ¹8 ³ m with increasing sintering temperature. This resulted in the disappearance of pores in the silver paste due to grain growth.…”
Section: Sintering and Electrical Propertiesmentioning
confidence: 94%